Analisis dampak yang ditimbulkan akibat keberadaan tempat pemrosesan akhir (TPA) Air Sebakul Kota Bengkulu - Mahdiya Fitri Lubis; Sopiah Sopiah; Ahmad Walid; Erik Perdana Putra (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2020)
Garbage is a result caused by human work so that in our daily life as humans we are always faced with what is called garbage. Waste disposal and processing methods are most widely applied in several cities in Indonesia, including Bengkulu City, which is located at the Final Processing Site (TPA). The existence of the TPA will have an impact on the environment. The problem that is important to be resolved is about environmental pollution, especially waste. The purpose of this study was to determine the impact that occurs due to the existence of TPA Air Sebakul Bengkulu City on the environment and local communities. This research method used literature-based methods, namely research to gather a variety of clarity of the problem in accordance with the research object. The result showed that the existence of TPA Air Sebakul had an impact on surrounding community in any aspects including economy, health, education, the environment, and social communities.